Relationship between number of substitutions, running performance and passing during under-17 and adult official futsal matches - Milanez, V. F.; Bueno, M. J. D. O.; Caetano, F. G.; Chierotti, P.; De Moraes, S. M. F.; Moura, F. A. (International Journal of Performance Analysis in Sport, 2020)
The aim of the study was to analyse the relationship between running performance and passes, as well as the effect of substitutions and the competitive level on these variables, during official futsal matches. Male juvenile athletes were filmed during five official games in the Youth Games competition and adult athletes were monitored during National League. The athletes were tracked to obtain their trajectories for subsequent quantification of physical actions, number of substitutions and passes during the games. Impairment in running performance, number of passes and number of substitutions were recorded using video cameras and analysed on a computer-based tracking system. The number of substitutions contributed singly to increasing total distance covered, very high-intensity running (%VHIR), and certain passes, regardless of possible differences between under 17 and adult categories. Players with a decrease in %VHIR presented lower (p = 0.039) pass efficiency (4% below). The adult players demonstrated that drop in running performance and successful passes in a futsal game may be observed from the second quarter, not only in the second half as shown in previous studies in futsal. Substitution of players is an important strategy to be used by coaches to improve running performance and passes in futsal games.